Analisis Implementasi PERMA No. 5 Tahun 2019 tentang Dispensasi Kawindan Dampaknya Terhadap Kesehatan Reproduksi Remaja di Kabupaten Sumenep - Fitriyah, Fitriyah; Khotimah, Khosnol (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the implementation of Supreme Court Regulation (PERMA) No. 5 of 2019 concerning Guidelines for Examining Marriage Dispensation Applications and its impact on adolescent reproductive health in Sumenep Regency. The research employs a combination of normative and descriptive qualitative methods with a socio-legal approach. Data were collected through document studies, interviews, FGDs, and field observations, and analyzed using triangulation of sources and methods. The findings reveal that although PERMA No. 5/2019 emphasizes the principle of the best interests of the child, in practice, decisions are still largely influenced by social, cultural, and economic factors. As a result, adolescents who marry early are exposed to reproductive health risks such as anemia, pregnancy complications, and stunting in children. This study highlights the urgent need for synergy between the judiciary, health sector, educational institutions, and village communities to reduce the prevalence of child marriage.